A new coil structure for implantable wireless charging system. (July 2021) - Chen, Jiajie; Xu, Jin
Highlights: Mathcad and Maxwell simulation were used to compare the mutual inductance coefficients of wireless charging under different radius ratios and different distances. The paper finds out the optimal radius ratio between the transmitting coil and the receiving coil, which greatly improves the transmission efficiency. The new coil structure proposed in this paper can effectively improve the transmission efficiency of the cardiac pacemaker, and the structure can play an anti-migration effect. Abstract: At present, wireless charging technology is widely used in implantable medical devices. However, the wireless charging system of implantable medical devices still faces problems such as low transmission efficiency and short transmission distance. A pacemaker is an implantable medical device. In view of the low transmission efficiency of the wireless charging system in current implantable cardiac pacemakers, this paper presents a new coil structure to achieve high efficiency transmission. The key to the design is to find the optimal radius ratio between the transmitting and receiving coils. The theoretical circuit diagram is given in the paper, and the theoretical analysis and formula derivation are carried out around the influence of radius ratio on the transmission efficiency and mutual inductance. Mathcad is used to simulate the influence of the radius ratio and transmission distance on the transmission efficiency and mutual inductance. Maxwell is further used to simulate magnetic field cloud diagrams under different radius ratios and transmission distances. Finally, the design parameters are used to build an experimental verification platform. Simulation and experiments show that the new coil structure proposed in this paper can improve the transmission efficiency of cardiac pacemaker.